Spy toys - Powers, Mark (London Bloomsbury, 2017)
The world's leading toy manufacturer makes playthings for the rich and famous, and every toy they create contains a tiny computerised brain and a unique personality. These toys are seriously awesome! But every so often there's a faulty toy...
3-5
Keywords: Language